microRNA function in left-right neuronal asymmetry: perspectives from C. elegans - Alqadah, Amel; Hsieh, Yi-Wen; Chuang, Chiou-Fen (Frontiers in Cellular Neuroscience, 2013)
Left-right asymmetry in anatomical structures and functions of the nervous system is present throughout the animal kingdom. For example, language centers are localized in the left side of the human brain, while spatial recognition functions are found in the right hemisphere in the majority of the population. Disruption of asymmetry in the nervous system is correlated with neurological disorders. Although anatomical and functional asymmetries are observed in mammalian nervous systems, it has been a challenge to identify the molecular basis of these asymmetries. C. elegans has emerged as a prime model organism to investigate molecular asymmetries in the nervous system, as it has been shown to display functional asymmetries clearly correlated to asymmetric distribution and regulation of biologically relevant molecules. Small non-coding RNAs have been recently implicated in various aspects of neural development. Here, we review cases in which microRNAs are crucial for establishing left-right asymmetries in the C. elegans nervous system. These studies may provide insight into how molecular and functional asymmetries are established in the human brain.